Continuity and Change in Academic Management Literature in Turkey: A Study on the 2000s - Dirlik, Serkan; Sehitoglu, Yasin (ISTANBUL UNIV, 2016)
This study examines the main features of management discipline in the 2000s by analyzing citations of management studies published in five academic journals in Turkey. Results show that some features used in previous years in literature have been maintained but some changes have also been observed. Management Research Journals which were analyzed in this study and started publishing articles in the 2000s were found to significantly differ from characteristics of Turkish management literature with regards to both approach and central concerns.
Keywords: INTELLECTUAL STRUCTURE; NATIONAL MANAGEMENT; Business & Economics